Concurrence of peripunctal nevus and uveal melanoma with scleral pigment dispersion presenting as phthisis bulbi. Issue 4 (16th April 2021) - Ghose, Neha; Vempuluru, Vijitha S; Jakati, Saumya; Kaliki, Swathi
Abstract : This case report demostrates an unusual occurence of peripunctal nevus and uveal melanoma, in which the clinical diganosis of uveal melanoma was masked by the atypical presentation as phthisis bulbi. Nevertheless, peculiar scleral pigment hinted at a possible intraocular tumour. The importance of meticulous clinical examination in assessment of ocular and periocular pigmented lesions is demonstrated. Further, clinicopathological differentials of correlation scleral pigmentation in diffuse necrotic uveal melanoma are illustrated.